Vad påverkas odlarna av i den svenska morotsodlingen? - Persson, Johan (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
In this degree project I write about how the farmers who grows carrots in Sweden get influenced by different rules, investments and demands. The Swedish agriculture are heading towards a harder time, and then you have to find new things to do. Now its hardly no profit to grow grain so you have find other crops. This paper is not a comparison between the contract cultivation to Findus and the cultivation where the farmer maked his products by a own company on the farm. If you have a small processing company on the farm, you have to increase the standard with different certificate. The farmer binds a lot of capital in machines, both field and in the process. They often take big economic risks to succeed. As a contract farmer to Findus, you have to follow their demands. The farmer doesen´t take so big risks and they doesn´t make any big investments. A big argument for the farmers is that, carrot growing should give better than the ordinary crops.